1998
DOI: 10.1007/s002709900227
|View full text |Cite
|
Sign up to set email alerts
|

Radiologically Guided Bone Biopsy: Results of 502 Biopsies

Abstract: Bone biopsy is a valuable technique for positive diagnosis of malignancy or infection, as it enables a definitive plan for treatment and management of patients to be established. Exclusion of serious pathology is almost equally important. In principle, any osseous site can be biopsied using fluoroscopic or computed tomographic guidance. Care in the biopsy technique and selection of the bone needle is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…The reported diagnostic yield of percutaneous biopsy of musculoskeletal lesions in the literature is 69%-90% [7][8][9][10][11][12][13][14]. Our success rate (in terms of diagnostic material yield) of 89% corresponds to the high end of the reported data.…”
Section: Discussionsupporting
confidence: 52%
“…The reported diagnostic yield of percutaneous biopsy of musculoskeletal lesions in the literature is 69%-90% [7][8][9][10][11][12][13][14]. Our success rate (in terms of diagnostic material yield) of 89% corresponds to the high end of the reported data.…”
Section: Discussionsupporting
confidence: 52%
“…Reported complication rates vary significantly, however most reports describe an approximately 1% rate, with 10% the highest described in the literature. 7,19,22,27,28,41 Complications may include excessive bleeding, neurological injury, infection, pain, and seeding of tumor cells, fracture and hematoma. 4,27 Studies have also shown the procedure to be safe in people with diabetes, with no major long-term complications of foot bone biopsy reported.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy of this procedure is reported at 85-92% [53], [54]. This level of success diminishes considerably in inexperienced operators and in biopsy of precariously placed lesions [54].…”
Section: A Biopsymentioning
confidence: 91%
“…Accuracy of this procedure is reported at 85-92% [53], [54]. This level of success diminishes considerably in inexperienced operators and in biopsy of precariously placed lesions [54]. Biopsy of the lumbar and thoracic spine report the highest levels of success and is the most routinely undertaken [55], [56].…”
Section: A Biopsymentioning
confidence: 98%